2010
DOI: 10.1021/es100397x
|View full text |Cite
|
Sign up to set email alerts
|

Precursors of Dichloroacetamide, an Emerging Nitrogenous DBP Formed during Chlorination or Chloramination

Abstract: Haloacetamides (HAcAms) are an emerging class of nitrogenous disinfection byproducts (N-DBPs). However, there is a limited understanding about the precursors of HAcAms. In this study, we screened the precursors of dichloroacetamide (DCAcAm), the most commonly identified HAcAm in chlorinated or chloraminated drinking water. DCAcAm formation potential (FP) of raw water samples collected in different months from a reservoir in China was determined during chlorination, and the highest DCAcAm FP typically occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
109
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(115 citation statements)
references
References 34 publications
5
109
1
Order By: Relevance
“…chain of an amino acid (Reckhow et al,2001;Chu et al, 2010b), where -CH 2 -is an 324 electron-donating group. The chlorine substitution reaction rate in -CH 2 -of Tyr was faster 325 than many other amino acids, probably because of the R-group including an aromatic 326 ring in the side chain of Tyr, which enhanced the electron-donating ability of -CH 2 -in the 327 main chain of Tyr (Chu et al, 2010b).…”
Section: /23mentioning
confidence: 99%
See 1 more Smart Citation
“…chain of an amino acid (Reckhow et al,2001;Chu et al, 2010b), where -CH 2 -is an 324 electron-donating group. The chlorine substitution reaction rate in -CH 2 -of Tyr was faster 325 than many other amino acids, probably because of the R-group including an aromatic 326 ring in the side chain of Tyr, which enhanced the electron-donating ability of -CH 2 -in the 327 main chain of Tyr (Chu et al, 2010b).…”
Section: /23mentioning
confidence: 99%
“…The chlorine substitution reaction rate in -CH 2 -of Tyr was faster 325 than many other amino acids, probably because of the R-group including an aromatic 326 ring in the side chain of Tyr, which enhanced the electron-donating ability of -CH 2 -in the 327 main chain of Tyr (Chu et al, 2010b). The aromatic ring in the R-group was probably 328 broken by a strong oxidizer (e.g., hydroxyl radical, Table S3 of Ala (Chu et al, 2009b).…”
Section: /23mentioning
confidence: 99%
“…The chlorine dose is almost proportional to the DOC value of water samples in DCAcAm FP test (Chu et al 2010b). All other disinfection conditions, i.e., reaction time (24 h), pH (7.5), and temperature (24°C), were kept constant in all trials.…”
Section: Model Development and Statistical Analysismentioning
confidence: 99%
“…These risks include formation of disinfection by-products (DBP), including trihalomethanes (THM), haloacetic acids, iodo-acids, halonitromethanes, nitrosamines, and dichloroacetamide that form when natural organics matter (NOM) reacts with chemical disinfectants [20,21]. Chow et al [19] reported that significant amounts of DBP precursors in sub-surface waters can be attributed to the leaching of organics from deciduous litter of surrounding vegetation, emphasizing the influence of catchment sub-surface water on reservoir water quality and consequently on DBP formation.…”
Section: Introductionmentioning
confidence: 99%
“…Chow et al [19] reported that significant amounts of DBP precursors in sub-surface waters can be attributed to the leaching of organics from deciduous litter of surrounding vegetation, emphasizing the influence of catchment sub-surface water on reservoir water quality and consequently on DBP formation. The concentration and character of DOM significantly influences raw and treated water quality and DBP formation [9,20,22].…”
Section: Introductionmentioning
confidence: 99%